An Empirical Analysis of Capital Structure and Long Term Solvency Position of Hindalco Industries Limited - Hiran, Sanjay Anandilal; Sojatia, Mahendra (Indian Journal of Finance, 2015)
The present study, through the application of ratio analysis and statistical techniques, determined the pattern of capital structure, long term solvency position, ability to pay fixed obligation to lenders, and proportion of debt in the capital structure of Hindalco Industries Limited. The duration of study is of 10 years - from the financial year 2003-04 to 2012-13. The results revealed that long term funds comprised of 86.69% of the total funds as compared to the short term funds, that is, 13.31% during the entire period under study. The company was using more owned funds, that is, 59.90% on an average than borrowed funds (26.79%). As per the results obtained, it can be concluded that Hindalco mostly preferred equity financing, so the financial risk of the company was low. But the company was not enjoying the benefits of capital gearing. The trend of interest coverage ratios were mixed, but the interest payment was fully covered by the earnings before interest and taxes. Hence, the study concluded that to enjoy the benefits of financial leverage, Hindalco Industries Limited should tap into the debt funds.